1998
DOI: 10.1210/jcem.83.10.5181
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Leptin Synthesis and Secretion Through Activation of Protein Kinases A and C in Cultured Human Trophoblastic Cells1

Abstract: Leptin is a fat cell-derived hormone that regulates food intake and energy expenditure. We previously demonstrated that leptin is produced by nonadipose cells, i.e. by placental trophoblasts. We also reported that a human trophoblastic cell line, BeWo cells, expresses leptin gene and secretes leptin into culture media. To elucidate the regulatory mechanisms of leptin production by human trophoblasts, we investigated synthesis and secretion of leptin in BeWo cells and in explant cultures of human placental tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Moreover, cAMP increased leptin promoter activity and leptin mRNA transcription . The stimulatory cAMP effect on the leptin expression was also reported in several cells such as glioma cells, pituitary tumor cells (Morash et al 2000, Li et al 2001, breast cancer cells (O'Neil et al 2001), gastric cells (Goiot et al 2005) and placental chorionic tissue (Yura et al 1998).…”
Section: Signal Transduction Pathways Mediating Leptin Inductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, cAMP increased leptin promoter activity and leptin mRNA transcription . The stimulatory cAMP effect on the leptin expression was also reported in several cells such as glioma cells, pituitary tumor cells (Morash et al 2000, Li et al 2001, breast cancer cells (O'Neil et al 2001), gastric cells (Goiot et al 2005) and placental chorionic tissue (Yura et al 1998).…”
Section: Signal Transduction Pathways Mediating Leptin Inductionmentioning
confidence: 63%
“…However, several experiments have evidenced that cAMP affects some cellular processes independently on PKA (Renstrom et al 1997, Cass et al 1999, Staples et al 2001. It was demonstrated that in BeWo cells and human-term placental tissue, leptin secretion is augmented by forskolin, an activator of PKA (Yura et al 1998). On the other hand, cAMP is known to alter human trophoblast function as demonstrated in numerous in vitro studies of normal and transformed trophoblast cells (Strauss et al 1992).…”
Section: Signal Transduction Pathways Mediating Leptin Inductionmentioning
confidence: 99%